Long‐term outcomes in healthy adults after radiofrequency ablation of T1a renal tumours. (8th November 2013) - Ma, Yunbo; Bedir, Selahattin; Cadeddu, Jeffrey A.; Gahan, Jeffrey C.
Abstract : Objective: To report the long‐term oncological and renal function outcomes in healthy adults treated with radiofrequency ablation (RFA) for small renal masses. Materials and Methods: We retrospectively analysed the medical records of otherwise healthy patients (those with American Society of Anesthesiologists symptom score 1 or 2) with clinical T1a renal tumours who underwent RFA at our institution between March 2001 and July 2012. Radiographic follow‐up with contrast imaging was performed at 6 weeks, 6 months, 1 year and annually thereafter. Local recurrence was defined as any new enhancing lesion (>10 HU) after the initial negative post‐treatment computed tomography results. The estimated glomerular filtration rates (eGFRs) before and after RFA were calculated using the Cockgroft–Gault equation. Results: We performed RFA on 58 renal tumours in 52 patients. The mean tumour size was 2.2 cm with a median (interquartile range) follow‐up of 60 (48–90) months. Three (5.1%) of the treated masses had tumour recurrence after initial RFA. The 5‐ and 10‐year recurrence‐free survival rate was 94.2%. There were no recurrences after 3 years. Three (5.1%) patients died during the follow‐up, which gave 5‐ and 10‐year overall survival rates of 95.7% and 91.1%. No patient developed metastatic renal cell carcinoma (RCC) and none died from RCC. Paired analysis showed that the eGFR values at a median follow‐up of 40 months did not differ significantly from those before RFA. Conclusion: With long‐term follow‐up, RFA provides durable oncological and functional outcomes for selected T1a renal tumours in otherwise healthy patients.